Gender Roles in Farming Systems: An Overview Using Cases from Ghana - Drafor, Ivy; Kunze, Dagmar; Hassan, Ramatu Al (Annals of Arid Zone, 2016)
The situation of hunger and poverty continues to persist despite recorded economic growth and democracy in Ghana. This presents the challenge to address the problems of small farmers, who produce most of the food. The improvement in small farmer livelihoods calls for sustainable farming systems that include the farm and non-farm economy and addresses gender perspectives for effective investment policies and development strategies. Agricultural programs and services are more effective when they are targeted within particular farming systems. There are also differentiated gender roles in farming systems with men and women playing vital, but complementary roles. Yet the limited access to, and control over resources by women compared to men, limits their productivities and therefore productivities of the whole system.